2002
DOI: 10.1007/s004420100792
|View full text |Cite
|
Sign up to set email alerts
|

Changes in interactions between juniper and mistletoe mediated by shared avian frugivores: parasitism to potential mutualism

Abstract: Although mistletoe is typically viewed as a parasite of juniper in a two-way interaction, its role may become neutral or even mutualistic when their common avian seed dispersing agents are considered as a three-way interaction. In the study area, wintering avian frugivores forage on both one-seed juniper (Juniperus monosperma) berries and on the fruit of its associated mistletoe (Phoradendron juniperinum). Three major findings emerged from our studies that support a three-way interaction and the hypothesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 40 publications
(58 reference statements)
0
42
0
1
Order By: Relevance
“…This favors the spread of seeds from infected hosts over noninfected hosts during years when susceptible trees have not produced an abundance of fruits. It has been suggested that when the seeds of infected trees are also spread by mistletoe vectors and this is correlated with greater tree regeneration, the relationship between the mistletoe and host tree approaches mutualism (Van Ommeren & Whitham 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This favors the spread of seeds from infected hosts over noninfected hosts during years when susceptible trees have not produced an abundance of fruits. It has been suggested that when the seeds of infected trees are also spread by mistletoe vectors and this is correlated with greater tree regeneration, the relationship between the mistletoe and host tree approaches mutualism (Van Ommeren & Whitham 2002).…”
Section: Discussionmentioning
confidence: 99%
“…When the mistletoe Phoradendron juniperinum was fruiting, removal of fruit from its host, Juniperus monosperma, was enhanced (van Ommeren and Whitham, 2002). Gleditsch and Carlo (2010) experimentally demonstrated increased fruit removal of Solanum americanum in areas that had higher shrub densities of Lonicera mackii and L. morrowii.…”
Section: Neighborhood Effectsmentioning
confidence: 99%
“…This favors the spread of seeds from infected hosts over noninfected hosts during years when susceptible trees have not produced an abundance of fruits. It has been suggested that when the seeds of infected trees are also spread by mistletoe vectors and this is correlated with greater tree regeneration, the relationship between the mistletoe and host tree approaches mutualism (213). Recent studies have also suggested other intriguing hypotheses regarding the interactions among host morphology, bird behavior, and mistletoe dispersal in South America (133,139).…”
Section: Mistletoe Biologymentioning
confidence: 99%
“…For dioecious tree species, bird visitation may be biased in favor of fruiting plants, thereby influencing overall mistletoe distribution (39). Furthermore, the consistent availability of mistletoe fruits can attract birds which also feed on the host's fruits (213). This favors the spread of seeds from infected hosts over noninfected hosts during years when susceptible trees have not produced an abundance of fruits.…”
Section: Mistletoe Biologymentioning
confidence: 99%
See 1 more Smart Citation